Overview of measurement in Growing Up in Australia - Zubrick, S; Ungerer, J; Harrison, L; Wake, M (My University, 2005)
Leaders of the design teams for Growing Up in Australia, the longitudinal study of Australian children (LSAC) will overview the measurement content in the study. Measurement is organised within domains of socio-demographics, child functioning, health, child care, education and family functioning. The measurement is designed to address the broad research questions of LSAC: How well are Australian children doing on a number of key developmental outcomes? What are the pathway markers, early indicators, or constellations of behaviours that are related to different child outcomes? How are child outcomes interlinked with their wider circumstances and environment? In what ways do features of children's environment (for example, families, communities and institutions) impact on child outcomes? Presenters will provide an overview of the content within the measurement domains. Comment will be made on the relevance and importance of that content in addressing the broad and the specific research questions that underpin LSAC. The focus is on the content of the 2004 Wave 1 data collection, for the birth and 4 year-old cohorts, obtained from the study informants who include parents, child care providers, and teachers, as well as the information obtained from direct assessment of children.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology